Pojęcie i nauka prawa wyznaniowego w Polsce - Tunia, Anna (Przegląd Prawno-Ekonomiczny, 2007)
Streszczenie dostępne wyłącznie w języku angielskim: In the following article the author presented the condition of ecclesiastical law as a seperate scientific branch in Poland. In this article the main trends of research (taken up lately by individual doctrine representatives), and the scope and nature of didactic classes in ecclesiastical law at Polish universities and colleges are discussed. Moreover she presented the differences in comprehending ecclesiastical law, introduced and characterized ecclesiastical law textbooks (available in Poland) and finally she portrayed the currently occuring phenomenon of consolidation of ecclesiastical law lecturers’ environment in Poland.